2002
DOI: 10.1086/338955
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thyroid Hormone Concentrations in a Wintering Passerine Bird: Their Relationship to Geographic Variation, Environmental Factors, Metabolic Rate, and Body Fat

Abstract: Winter acclimatization among passerine birds involves metabolic adjustments that allow for high rates of thermogenesis. In previous studies, we observed geographic variation in the basal metabolic rate (BMR) of overwintering cardinals along a latitudinal gradient at two different longitudinal transects. Because thyroid hormones (THs) are important for metabolic adjustments in endotherms, we determined whether geographic variation in BMR can be explained by variation in thyroid status. We measured total plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…The lower sensitivity of the pituitary-thyroid axis to TRH stimulation is due to the elevated serum T3 levels. The higher T3 levels at cold temperature and the positive correlation between T4 and temperature seem to be general patterns in birds (Dawson et al, 1992;Burger and Denver, 2002). Although most of the studies explain the seasonal variation in THs by an increased food intake in response to cold temperature, our results fail to support this hypothesis.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The lower sensitivity of the pituitary-thyroid axis to TRH stimulation is due to the elevated serum T3 levels. The higher T3 levels at cold temperature and the positive correlation between T4 and temperature seem to be general patterns in birds (Dawson et al, 1992;Burger and Denver, 2002). Although most of the studies explain the seasonal variation in THs by an increased food intake in response to cold temperature, our results fail to support this hypothesis.…”
Section: Discussioncontrasting
confidence: 83%
“…Another important branch of thyroid surveys deals with the decrease in quality or quantity of prey-availability of top predators. Nutritional stress can alter metabolic rate and affect overwintering via reduced body reserves in temperate climates, which can drive the change in survival and population dynamics (Northern cardinal: Burger and Denver, 2002; harbour seal: Oki and Atkinson, 2004). Finally, impacts of endocrine disrupters are very considerable topics of scientific discussion, since agricultural pollution has remained an unsolved phenomenon for decades (Bowerman et al, 2000;Scollon et al, 2004).…”
mentioning
confidence: 99%
“…Ten individuals were sampled in both a dry season and a moist season, thus resulting in a total of 71 blood samples for analysis of T 3 , glucose and ketone levels (dry season: 25 females and 21 males; moist season: 11 females and 14 males). We took blood samples early in the morning shortly after mice emerged from their nest, to control for possible circadian rhythms in hormone excretion (Burger and Denver, 2002). We captured individuals using Sherman-style live-traps (26×9×9 cm), which were placed close to a group's nest.…”
Section: Blood Sampling and Hormone Assaysmentioning
confidence: 99%
“…However, little information is available concerning the relationship between thyroid hormones and metabolic rate for animals living under natural conditions (exceptions are studies on birds: Chastel et al, 2003;Elliott et al, 2013;Welcker et al, 2013;Zheng et al, 2014; and a study of free-ranging Arctic ground squirrels Urocitellus parryii; Wilsterman et al, 2015), and the reported results are ambivalent. Some studies report a positive relationship between T 3 levels and metabolic rate (Chastel et al, 2003;Welcker et al, 2013) while others found no relationship (Burger and Denver, 2002). This inconsistency in results highlights the need for additional studies examining the relationship between thyroid hormone levels and metabolic rate of free-living animals, especially mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma total T4, free T4, and total T3 levels of sled dogs living in Alaska were higher than dogs in New York, especially in winter [60]. In addition, plasma T3 increased with increasing latitude in the northern cardinals Cardinalis cardinalis, whereas plasma T4 did not show a simple latitudinal cline: both southern and northern birds had higher T4 levels than birds living at an intermediate latitude [61]. In mammals, bottlenose dolphins Tursiops truncatus show variation in thyroid hormone concentrations between populations inhabiting different latitudes [62]: plasma total T3 and T4 were higher in dolphins from South Carolina with colder year-round temperatures than those from Florida with much warmer water temperatures.…”
Section: Inter-population and Geographical Variation In Thyroid Hormomentioning
confidence: 79%